Pengaruh Lingkungan Kerja Terhadap Kepuasan Kerja pada Dinas Koperasi, Perindustrian dan Perdagangan Kota Bima - Fani Putra Bimantara; Jaenab Jaenab; Muhammad Yusuf; Siti Asyitah (Indo Publishing, 2026)
This study aims to determine whether the work environment has a significant effect on employee job satisfaction at the Department of Cooperatives, Industry, and Trade of Bima City. This is an associative study. Purposive sampling was employed to select 40 respondents. A questionnaire utilizing a Likert scale served as the research instrument. Data analysis involved validity and reliability testing, as well as simple linear regression, with the data processed using SPSS version 21. The results indicate that the work environment has a significant effect on job satisfaction at the Department of Cooperatives, Industry, and Trade of Bima City.